Effects of a Multifaceted Education Program on Enrollment, Learning, and Gender Equity : Evidence from Rajasthan, India - Delavallade, Clara (World Bank, Washington, DC, 2021)
The Sustainable Development Goals set a triple educational objective: improve access to, quality of, and gender equity in education. This note documents the effectiveness of a multifaceted educational program pursuing these three objectives simultaneously. Using an experiment in 229 schools in rural Rajasthan, India, this study measures the effects of the program on students’ school participation and academic performance over two years, as well as its heterogeneous impacts by gender and initial learning ability. The findings show that the program increased student enrollment and retention, with the largest effects observed among girls. There is no evidence that the program differentially attracted lower-ability students. There were large learning gains in both years, where the learning outcomes of boys and girls improved equally. These findings suggest that multifaceted interventions can overcome the tradeoffs that often arise when pursuing multiple objectives in educational interventions.